2018
DOI: 10.1074/jbc.ra118.003161
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator–activated receptor γ (PPARγ) induces the gene expression of integrin αVβ5 to promote macrophage M2 polarization

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a member of the nuclear receptor superfamily and polarizes the macrophages into an anti-inflammatory M2 state. Integrins are transmembrane receptors that drive various cellular functions, including monocyte adhesion and foam cell formation. In this study, we first reported that the expression of integrins α and β was up-regulated by PPARγ activation in RAW264.7 cells and human peripheral blood monocytes. Luciferase reporter and ChIP assay revealed that PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 43 publications
5
46
0
Order By: Relevance
“…In addition to the expression in monocytes and macrophages, PPAR-γ was shown to inhibit monocyte differentiation into macrophages and to be crucial for macrophage M2 polarization [27,30], thus reducing the inflammatory cascade.…”
Section: Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the expression in monocytes and macrophages, PPAR-γ was shown to inhibit monocyte differentiation into macrophages and to be crucial for macrophage M2 polarization [27,30], thus reducing the inflammatory cascade.…”
Section: Functionsmentioning
confidence: 99%
“…Polyunsaturated fatty acids are related to the modulation of inflammation; in particular, they are responsible for a decrease of the production of pro-inflammatory cytokines through activation of PPAR-γ [30]. Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are contained in sea food and fish oil, and they are involved in the inhibition of various aspects of inflammation, such as leucocytes chemotaxis, adhesion molecule expression, and eicosanoid production.…”
Section: Sea Food and Fish Oilmentioning
confidence: 99%
“…Lee and colleagues found that YAP/TAZ participates in the regulation of 135 genes in macrophages, of which 66 were closely related to cell development, differentiation, metabolism, and immunity, including PPARg, myoblast determination protein (MyoD), the zinc finger of the cerebellum 1 (Zic1), and lymphocyte function-associated antigen 1 (LF-A1) (87). The transcription factor PPARg has also been reported to modulate the polarization and inflammatory responses of macrophages (42,43,93). YAP/TAZ plays a crucial role in the biological activity of macrophages.…”
Section: Yap/taz In Regulating Macrophagesmentioning
confidence: 99%
“…[35][36][37][38][39]. Phosphorylated YAP/TAZ recruits the E3 ubiquitin ligase SCF (b-TRCP) to induce its ubiquitination and proteasomal degradation (40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the anti-inflammatory effect of TatM013 in the retina, we isolated RNA from eyes treated with either sGFP or sGFP-TatM013 and used RT-qPCR to measure the gene expression differences between these groups. Retinas treated with the sGFP-TatM013 had significant increases in IL-27Ra and Ppar-γ, both of which are associated with anti-inflammatory macrophages [37,38], when compared to the sGFP treated retinas (Table 3). Furthermore, when we measured the expression of pro-inflammatory genes, we found that sGFP-TatM013 treated retinas had significantly lower expression of IL-17A and C3 when compared to sGFP treated retinas (Table 3).…”
Section: M013 Changes Gene Expression Pattern In the Retina Of Eau Micementioning
confidence: 99%